Genetic Identification of Brazilian Mammalian Hosts of Trypanosoma cruzi: Improving Blood Meal Source Discrimination in Vector-Borne Transmission - Quezia Moura Oliveira; Thaíla Santos Pessanha; Alena Mayo Iñiguez (Pathogens)
The detection of food sources of blood-sucking vectors is essential for a better understanding of the hosts, reservoirs, and other fauna that participate in the transmission web of hemoparasites. The molecular identification of triatomine blood meal sources (BMSs) has been shown to be highly sensitive and taxonomically specific when compared to the immunological method. The application of molecular cloning makes it possible to identify multiple BMS species and/or different individuals/haplotypes of the same vertebrate species in a single triatomine specimen. In Brazil, the molecular detection of BMSs is incipient, with insufficient genetic information on the species of animals involved in the transmission of Trypanosoma cruzi. In this work, we evaluated the sensitivity and specificity of a molecular approach using molecular cloning for the detection of multiple Brazilian mammalian species. The DNA was extracted from blood clots of 13 species of canids, bats, xenarthral, marsupials, and rodents. Serial proportions were used to formulate mixtures combining taxonomically close (belonging to the same family or order) and taxonomically distant (different families) species. The results showed that GenBank lacks reference sequences for some native species tested, such as the sylvatic rodent, Necromys lasiurus, and the wild canid, Lycalopex gymnocercus, for cytb and 12S rDNA, and the rodent Oecomys cleberi for 12S rDNA. The study also demonstrated that it is possible to detect multiple different species, even for those that are taxonomically close. This approach was proven to be efficient for the detection of species in equal and even in disparate unequal proportions, which could represent complementary information about the diversity of potential hosts of T. cruzi. The detection of multiple BMS species in mixed samples provides a more comprehensive and accurate landscape of T. cruzi transmission in nature.